The effect of government expenditure, economic growth, and population on employment and poverty in East Kalimantan Province (Indonesia) - Wibowo, Sigit; Wijaya, Adi; Irwansyah, Irwansyah (Technium Social Sciences Journal, 2021)
The sustainability of regional development cannot be separated from the role of the government in overcoming social and economic problems. This study aims to analyze the direct and indirect linkages of government expenditure, economic growth, and population to employment and poverty in East Kalimantan Province. A quantitative-based study approach involving secondary data support. Time series data for 2010-2020 are presented through path analysis techniques. Hypothesis testing is carried out in several stages, starting from the feasibility test of the model, the simple assumption test, partial test, simultaneous test, and the calculation of the indirect effect through the single test. As a result, in structure 1, it is evident that government expenditure and population have a positive and significant effect on employment. From structure 2, only economic growth is ideal or has a negative and significant effect on poverty. As for the indirect effect, government expenditure and population have a negative and insignificant effect on poverty through employment. This also indicates that of the ten proposed hypotheses, only half or five of the hypotheses can be accepted. On the other hand, the other five hypotheses have been rejected.